The Association between Fat-Free Mass and Exercise Test Outcomes in People with Chronic Obstructive Pulmonary Disease: A Systematic Review. Issue 1 (31st December 2022) - Gaynor-Sodeifi, Kaveh; Lewthwaite, Hayley; Jenkins, Alex Robert; Fernandes Belo, Letícia; Koch, Emily; Mujaddid, Ahzum; Raffoul, Dana; Tracey, Lauren; Jensen, Dennis
Abstract: People with chronic obstructive pulmonary disease (COPD) tend to have abnormally low levels of fat-free mass (FFM), which includes skeletal muscle mass as a central component. The purpose of this systematic review was to synthesise available evidence on the association between FFM and exercise test outcomes in COPD. MEDLINE, Cochrane Library, EMBASE, Web of Science, and Scopus were searched. Studies that evaluated exercise-related outcomes in relation to measures of FFM in COPD were included. Eighty-three studies, containing 18, 770 (39% female) COPD participants, were included. Considerable heterogeneity was identified in the ways that FFM and exercise test outcomes were assessed; however, higher levels of FFM were generally associated with greater peak exercise capacity. This association was stronger for some exercise test outcomes (e.g. peak rate of oxygen consumption during incremental cycle exercise testing) than others (e.g. six-minute walking distance). This review identified heterogeneity in the methods used for measuring FFM and exercise capacity. There was, in general, a positive association between FFM and exercise capacity in COPD. There was also an identified lack of studies investigating associations between FFM and temporal physiological and perceptual responses to exercise. This review highlights the significance of FFM as a determinant of exercise capacity in COPD.